APPLICATION OF ENVIRONMENTAL ACCOUNTING TO HIU PAUS TOURISM IN TOMINI BAY - Kanon, Juwita; Amaliah, Tri Handayani; Badu, Ronald Soemitro (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This study examines the application of environmental accounting in Hiu Paus Tourism in Tomini Bay.Research Methods. This research is in the realm of qualitative study using a phenomenological approach.Research Results and Findings. The results showed that Hiu Paus Tourism still needs to implement environmental accounting by PSAK 2015 No. 1 concerning the presentation of financial statements, and there has been no special report related to environmental costs. In environmental management, Hiu Paus Tourism has carried out waste management and maintenance of coral reefs internally. However, the allocation of environmental costs is still carried out and has not been maximized. However, Hiu Paus tours in Tomini Bay have followed general rules of interaction for the safety of visitors in special interest tours.